Smoking Induces the Circulating Levels of Matrix Metalloproteinase-9 and Its Association with Cardiovascular Risk in Young Smokers - Dinesh NATH; Meera SHIVASEKAR; V. M. VINODHINI (Medeniyet Medical Journal)
Objective: Smoking causes cardiovascular risk, which may alter the stability between the production and degradation of the extracellular matrix. Matrix metalloproteinase-9 (MMP-9) is a zinc-containing endopeptidase that degrades the extracellular matrix and is involved in tissue remodelling and several physiological processes. As a result, smoking-induced elevated serum MMP-9 levels, particularly at a younger age, raise the risk of coronary heart disease (CHD). Thus, this study aimed to determine the possible relationship between smoking-induced circulating MMP-9 and the risk of cardiovascular disease in young smokers. Methods: In this cross-sectional study, the patients were divided into three groups. Each group contains 120 study participants. Group one consisted of 120 healthy individuals with no physical and mental illness, group two consisted of 120 active smokers with a heart disease, and group three consisted of 120 active smokers with a heart disease and diabetes, who attended Sri Ramaswamy Memorial Hospital for cardiology checkup at the age of 20-55 years. The serum MMP-9, high-sensitivity C-reactive protein (hs-CRP), and apolipoprotein-E (APO-E) levels were analyzed using the ELISA method, and the lipid levels were measured enzymatically using AU480 automatic analyzer (Beckman Coulter). Results: Compared with non-smokers, the study shows that the mean serum MMP-9, hs-CRP, and APO-E levels were significantly higher in smokers (p<0.001). A strong relationship was also found between MMP-9 and hs-CRP, APO-E, smoking load, and smoking intensity. Conclusions: A significant association was found between cigarette smoking with MMP-9, and relative exposure to circulating inflammation markers plays a potential role in the pathogenesis of CHD.